Síntese, caracterização e aplicação de ligantes geopoliméricos em concretos refratários avançados - Bezerra, Breno Parente (2024)
Alternative binders represent a promising avenue for the development of ultra-low and cement-free refractories, significantly reducing CO2 emissions and the energy consumption associated with these products. Geopolymers (GP) are sustainable binders that can be utilized in the manufacture of these ceramics. However, a comprehensive comparison of systems containing calcium aluminate cement (CAC) or GP is necessary to identify the advantages and limitations of these new materials. In this study, the synthesis, characterization, and application of geopolymers in alumina-based castables were evaluated, aiming to enable the partial or complete replacement of CAC in these refractories. Initially, metakaolin (MK)-based geopolymer systems were formulated using liquid reagents (LR) composed of NaOH and different sources of amorphous silica (sodium silicate, silica fume, or colloidal silica suspension). Subsequently, the most promising LR was chosen, adjusting the content of NaOH and/or KOH to enhance the thermal stability of the geopolymers. Furthermore, the effect of incorporating these new binders into the properties of the refractories was investigated between 40-1400°C through various tests, including flowability, physico-thermo-mechanical measurements, and XRD, ATR-FTIR, and/or SEM analyses. Geopolymers prepared with colloidal silica suspension (CS) exhibited the best characteristics for use in the development of innovative refractories. Alumina-based castables with 8 wt.% MK and LR containing NaOH-CS (8MK-Na) and 6 wt.% MK and LR containing KOH-CS (6MK-K) showed optimized behavior, where the generation of a liquid phase during sintering induced densification of the samples between 1100-1250°C. These transformations resulted in microstructures with strong interfacial bonds between the glassy phase and alumina grains. Additionally, the refractory containing a combination of 2.7 wt.% CAC and 1.3 wt.% MK exhibited 1.18% shrinkage, an elastic modulus of 135 GPa, mechanical strength of 39.1 MPa, and high thermal shock resistance. These advancements resulted in the development of refractories with remarkable performance, surpassing the reference material.